Behdinan’s Movements Against British Colonialism After the First World War 1918-1920 - Qader, Ali M. (Humanities Journal of University of Zakho, 2015)
The research seeks to identify those movements carried out by the people of Behdinan against British occupation forces; this uprising is one of the most important steps taken by Kurdish rebel in 1919 for the liberty of Kurdistan from the British restrictions. It was also the preface of the outbreak of the Iraqi Revolution named (The Revolt of Twentieth). But, despite the importance of this subject, it has not received the attention of the majority of historians who talked about the situation of the Kurdistan after the First World War. However, the writer Abdel Moneim Al Ghulam was the only one who wrote on such a topic in detail in his book (Our Revolution in Northern Iraq).There were several motives behind the outbreak of the revolution, including: poor British administration, which offended the British to act against the people of the region, as well as, the religious factor that pushed the Kurds to resist the British occupation in Badinan area, and also the promises given by the British government to Assyrian in order to create an Assyrian state in the area and resettle them in the Kurdish villages was another factor to the revolution. Another motivation was that propaganda which carried out by the Turkish government in Badinan area in order to link the state of Mosul with the Turkish border.These factors led to the outbreak of a lot of movements in Behdinan area in order to expel the British presence in the region, which are: the movement of the people of Zakho (Goyan) on 4 April, 1919, the movement of Amadiyah people on July 15, the Battle of the Gelly Mizirka on 8 August, the battle of Swaretoka on 22 August and finally, the uprising of Akre and Zebar on 4 November of the same year. As a result, all of these movements led to the killing of many of the rebels with some of the British troops in those battles that took place between them. These movements did not last for a long time because of the lack of sufficient military experience and weapon among the rebels.